Denitrification of surface and ground water applying autohydrogenotrophic bacteria in a novel upflow bio-electrochemical reactor(UBER) - Ghafari, S.; Hasan, M.; Aroua, M.K. (2009)
Nitrates in different surface and groundwater resources became a worldwide problem which raised concerns due to severe impacts on human and animal health. Although diverse abiotic methods were reported to remove nitrate from water, they fail to entirely treat nitrate. Biological denitrification is the only treatment method capable to reduce inorganic nitrate compounds to harmless nitrogen gas. Autohydrogenotrophic denitrifiers were applied in this study to prevent any problematic outcomes of heterotrophs’ metabolisms raised from organic carbon source. A novel upflow bio–electrochemical reactor (UBER) was designed and employed to generate in-situ hydrogen and fulfill denitrifying process at cathode zone. Granular activated carbon (GAC) utilized to play a dual role as biocarrier and cathode material. Simple but effective design of this reactor helped to easily control the operating parameters such as electric current and flowrate. Furthermore, employing a circulating system, this reactor succeeded to cope with accumulation of nitrite in the cathode zone, which is known as a common and problematic phenomenon inhibiting the reaction.